Correlates of satisfaction in religious life among the members of the Handmaids of Mary - Pulickakunnel, Marykutty Varkey (Animo Repository, 1984)
This descriptive study was undertaken to find out the level of satisfaction experienced by the members of the Handmaids of Mary, India, in the areas of community life, spiritual life and apostolic life and its relationship with self-concept. Also, to investigate if there was a difference in satisfaction with regards to size of the family, ordinal position, number of years in religious life and educational attainment of the respondents. The subjects of the study were 140 sisters randomly selected from the total population of 286. The instruments used in this study were Tennessee Self-Concept Scale, questionnaire to assess the level of religious satisfaction and a personal information sheet. The instruments were sent to India and sufficient copies were made there. The data were mailed back to the researcher. The initial statistical analysis of the data brought out the level of religious satisfaction in the three areas namely community life, spiritual life and apostolic life. Pearson r was computed to find out the relationship between the variables and t tests to find out the difference in satisfaction in relation to the variables under the study. The results of the study showed that the respondents were some what satisfied in community life, spiritual life and apostolic life. There was a significant (.05 level) positive but low correlation between satisfaction in community life (.21) and self-concept and between satisfaction in apostolic life and self-concept (.17). There was no significant relationship between satisfaction in spiritual life and self-concept. There was no difference in satisfaction with regards to the size of the family, ordinal position, number of years in religious life between the respondents. However, there was a significant difference in satisfaction between the respondents who are lower and higher in educational attainment. Those who are in high educational attainment were less satisfied in religious life compared to those who were low in educational attainment. Based on the findings the following conclusions were made. Religious satisfaction has a significant relationship with self-concept. Among the subscales of self-concept personal self and social self had significant bearing in relations to religious satisfaction. The only environmental factor that has any bearing on satisfaction in religious life seemed to be educational attainment.